PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP MOTIVASI KERJA GURU DI SEKOLAH MENENGAH PERTAMA NEGERI 21 BATANG HARI - Anjuna Cahya Azzahra; Sukatin Sukatin; Zilawati Zilawati (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to describe, test and analyze the influence of the work environment and compensation on teacher work motivation at the 21 Batang Hari State Junior High School. This type of research is quantitative using a survey approach. To obtain the researched data, researchers took population data, namely all 33 teachers at Batang Hari 21 State Junior High School. The methods used were questionnaires and documentation, then the researchers carried out multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS). The results of this research can be concluded that there is a significant influence of the work environment on teacher work motivation of 55.6%, meaning that the better the work environment at the Batang Hari 21 State Junior High School, the better the teacher's work motivation. There is a significant influence of compensation on teacher work motivation of 43.1%, meaning that if compensation is carried out clearly and appropriately, the teacher's motivation will be even better. This shows that the work environment and compensation both have a significant influence on teacher work motivation by 94.2%. Based on the results of this research, it can be concluded that the research hypothesis which states "The Influence of the Work Environment and Compensation on Teacher Work Motivation" is acceptable.